Child-to-Child Interaction and Corrective Feedback in a Computer Mediated L2 Class - Frank Morris (Language Learning and Technology, 2005)
The current study examined the provision of corrective feedback and learner repair following feedback in the interactional context of child-to-child conversations, particularly computer mediated, in an elementary Spanish immersion class. The relationship among error types, feedback types, and immediate learner repair were also examined. A total of 46, fifth-grade children participated in the study. Using Blackboard, the instructor randomly paired students and created a "virtual group" for each pair. Each pair was asked to interact and complete a jigsaw task in the "virtual classroom." Blackboard recorded the pairs' interactions, which were later printed and coded for types of error (syntactic/lexical), types of negative feedback (explicit/recasts/negotiation) and immediate learner repairs. Findings indicate that learners did not provide explicit negative feedback. Learners provided implicit negative feedback (recasts and negotiation) while completing the jigsaw task in the virtual classroom. The majority of lexical errors and syntactic errors were corrected using negotiation. Over half of feedback moves led to immediate repair. Negotiation moves proved more effective at leading to immediate repair of errors than did recasts.